Passive Conservation of Manuscripts in Libraries - Nil Baydar (Türk Kütüphaneciliği)
The purpose of this study is examination of the deterioration factors (moisture, temperature, light, weather pollution, disasters, rodents, insects and microorganisms) of the manuscripts with mishandling of both library staff and readers in libraries and giving preventive conservation suggestions.